Evidence of Austronesian Genetic Lineages in East Africa and South Arabia: Complex Dispersal from Madagascar and Southeast Asia. (4th February 2019) - Brucato, Nicolas; Fernandes, Veronica; Kusuma, Pradiptajati; Černý, Viktor; Mulligan, Connie J; Soares, Pedro; Rito, Teresa; Besse, Céline; Boland, Anne; Deleuze, Jean-Francois; Cox, Murray P; Sudoyo, Herawati; et al.
Abstract: The Austronesian dispersal across the Indonesian Ocean to Madagascar and the Comoros has been well documented, but in an unexplained anomaly, few to no traces have been found of the Austronesian expansion in East Africa or the Arabian Peninsula. To revisit this peculiarity, we surveyed the Western Indian Ocean rim populations to identify potential Austronesian genetic ancestry. We generated full mitochondrial DNA genomes and genome-wide genotyping data for these individuals and compared them with the Banjar, the Indonesian source population of the westward Austronesian dispersal. We find strong support for Asian genetic contributions to maternal lineages and autosomal variation in modern day Somalia and Yemen. Surprisingly, this input reveals two apparently different geographic origins and timings of admixture for the Austronesian contact; one at a very early phase (likely associated with the early Austronesian dispersals), and a later movement dating to the end of nineteenth century. These Austronesian gene flows come, respectively, from Madagascar and directly from an unidentified location in Island Southeast Asia. This result reveals a far more complex dynamic of Austronesian dispersals through the Western Indian Ocean than has previously been understood and suggests that Austronesian movements within the Indian Ocean may have been part of a lengthy process, probably continuing well into the modern era.